Carotid Artery Involvement in Patients Undergoing Coronary Angiography with Diabetes Mellitus (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Carotid artery disease would be high in patients having coronary artery disease with diabetes mellitus.Objective: The purpose of the present study was to see frequency, pattern and severity of carotid artery disease among patients with IHD and diabetes mellitus.Methodology: This case-control study was conducted in Department of Cardiology, UCC, BSMMU from July, 2007 to June 2009. Total 100 patients were included in this study. Of them 50 patients were coronary artery disease with diabetes mellitus and another 50 patients were coronary artery disease without diabetes mellitus. Both group were underwent coronary and carotid angiography. Coronary artery stenosis is assessed by different scoring system and carotid artery stenosis are categorized as mild (< 50% stenosis) moderate (50-69% stenosis) and critical (>_ 70% stenosis). Moderate and critical stenosis was considered as significant carotid artery disease. Morphological character of the lesion was also assessed.Results: The mean age was found 57.48 years with 6.04 standard deviation (SD) in DM and 55.64 years with 6.34 standard deviation in NDM group and also 56.56 years with 6.49 standard deviation in the whole study population. the indications of CAG were Post MI evaluation, unstable angina, stable angina, chest pain evaluation and positive ETT were 42.0%, 20.0%, 18.0%, 10.0% and 10.0% in DM group and 32.0%, 28.0%, 20.0%, 8.0% and 12.0 in NDM group respectively. LAD was the commonest artery involved (86.0%), followed by RCA (82.0%), LCX (68.0%) and LM (6.0%) in DM study subjects. Among the NDM LAD artery involved (76.0%), followed by RCA (72.0%), LCX (64.0%) and LM (4.0%) in NDM study subjects.Conclusion: In conclusion, patients of coronary artery disease with diabetic mellitus are having higher frequency and severity of Carotid artery disease than non-diabetic coronary artery disease patients.Journal of National Institute of Neurosciences Bangladesh, January 2023;9(1):30-34